THE SULFONATION STUDY OF REACTION MECHANISM ON PAPAVERINE ALKALOID BY GC-MS AND FT-IR - I Made Sudarma (Indonesian Journal of Chemistry, 2007)
The aim of this research was to prove theoretical mechanism reaction on the sulfonation of papaverine alkaloid and the result could be used as a reference on the transformation of these alkaloid to the other derivatives. Theoriticaly sulfonation of papaverine (1) by HO-SO2Cl could produced papaverine sulfonyl chloride (1a). The formation of this product was analyzed by analytical thin layer chromatography GC-MS, and FT-IR. These analysis showed the formation of product (1a) more favorable than the other. Tlc showed product (1a) less polar than papaverine, and supported by GC-MS and infrared which showed molecular ion at m/z 412 due to the presence of -SO2Cl and vibration at 1153,4 dan 1265,2 Cm-1 due to absorption of sulfonyl group.